2013
DOI: 10.1177/0143034312469157
|View full text |Cite
|
Sign up to set email alerts
|

Effects on coping skills and anxiety of a universal school-based mental health intervention delivered in Scottish primary schools

Abstract: Anxiety disorders are common in children and may signal risk of depression, social or academic difficulties. This study evaluated the effects of a universal mental health promotion intervention delivered in primary schools. Three hundred and seventeen 9 to10 year olds were randomly allocated by class group to intervention condition (psychologist-led or teacher-led), or comparison condition. Coping and anxiety were measured pre- and post-intervention and at six month follow-up. Significant anxiety reduction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 50 publications
0
53
0
6
Order By: Relevance
“…Help‐seeking and coping skills were identified as outcome measures in 14 of the 29 studies. Reduction in stress postintervention was reported by nine authors (Campion & Rocco, ; De Anda, ; De Villers & Van Den Berg, ; De Wolfe & Saunders, ; Hampel, Meier, & Kummel, ; Kraag, Van Breukelen, Kok, & Hosman, ; Kuyken et al., ; Metz et al., ; Schonert‐Reichl et al., ), whilst five (Collins, Marks Woolfson, & Durkin, ; King, Strunk, & Sorter, ; Merrell, Juskelis, Tran, & Buchanan, ; Mishara & Ystgaard, ; Rickwood, Cavanagh, Curtis, & Sakrouge, ) found no improvement. Four authors (De Anda, ; Kraag et al., ; Merrell et al., ; and Mishara & Ystgaard, ) reported increases in the coping skills and strategies used by children that received interventions.…”
Section: Resultsmentioning
confidence: 91%
“…Help‐seeking and coping skills were identified as outcome measures in 14 of the 29 studies. Reduction in stress postintervention was reported by nine authors (Campion & Rocco, ; De Anda, ; De Villers & Van Den Berg, ; De Wolfe & Saunders, ; Hampel, Meier, & Kummel, ; Kraag, Van Breukelen, Kok, & Hosman, ; Kuyken et al., ; Metz et al., ; Schonert‐Reichl et al., ), whilst five (Collins, Marks Woolfson, & Durkin, ; King, Strunk, & Sorter, ; Merrell, Juskelis, Tran, & Buchanan, ; Mishara & Ystgaard, ; Rickwood, Cavanagh, Curtis, & Sakrouge, ) found no improvement. Four authors (De Anda, ; Kraag et al., ; Merrell et al., ; and Mishara & Ystgaard, ) reported increases in the coping skills and strategies used by children that received interventions.…”
Section: Resultsmentioning
confidence: 91%
“…It's widely accepted how complex interactions between genetic and environmental factors affect the onset and the maintenance of depressive symptoms [6,16,17]. Nevertheless, this symptomatology would differently manifest depending on the gender and the age.…”
Section: Depression In Childrenmentioning
confidence: 99%
“…In this field, Steca et al [17], highlighted the role of self-esteem; when pupils face a challenging or threatening task aimed at evaluating their competences, a low self-worth may affect their mood. However, a low self-worth can obstacle social relationships with classmates by encouraging feelings of isolation and depressed behaviors.…”
Section: Depression In Childrenmentioning
confidence: 99%
“…With respect to other wellbeing outcomes, coping skills interventions were shown to increase social skills (Mishara and Ystgaard 2006), assertiveness (Schinke et al 1987) and self-efficacy (Frydenberg et al 2004, Study 3). The interventions were also found to decrease anxiety (Collins et al 2014), reduce behavioural problems and reduce social problems (Mishara and Ystgaard 2006;Monkeviciene et al 2006). However, the researchers found no significant effects on self-esteem (Schinke et al 1987), emotional symptoms (Holen et al 2012) peer relations (Schinke et al 1987) and prosocial behaviour (Holen et al 2012).…”
Section: Pathway Five: Copingmentioning
confidence: 96%
“…Holen et al (2012) found a significant increase in parent-rated (but not self-rated) active coping for intervention children and decreased oppositional coping, but no effects for emotional regulation or withdrawal coping. Other programs found students who completed a coping intervention generated significantly more problem-solving options (Schinke et al 1987), and significant decreases in avoidance coping and significant increases in problem-solving and seeking social support, relative to a control groups (Collins et al 2014).…”
Section: Pathway Five: Copingmentioning
confidence: 99%